Small holder cattle farming in East Coast Economic Region (ECER), Malaysia: Farmers’ perception on type, breed and crosses - Amal Najim; Md. Ruhul Amin; S.M.R. Karimand; Soon Jan Mei (2015)
Breed and types of cattle in the small holder farming system were investigated by direct survey method in East Coast Economic Region (ECER), Malaysia. A group of 508 cattle farmers operating in the region were the participants of the study. Data were collected by administering a questionnaire filled during the face to face interviews conducted with each individual respondent. Results showed that beef type cattle predominate in all the states with a range of 81.98 to 97.49% but 18.01% dairy cattle exist in Mersing district of Johor. Holstein Friesian (HF), Jersey (Jer), Local Indian Dairy (LID), Mafriwal (Maf) and different crossbreeds constitute the dairy cattle population. Beef cattle industry consists of both tropical and temperate cattle. Kedah Kelantan (KK), Brahman (Brah) and Bali cattle comprises the Bos indicus group while Limousin (Lim), Belgian Blue (Belg), Angus (Ang), Charolais (Char) made up the Bostaurus group. KK–exotic crosses are also abundant. Farmers of Johor have more inclination to dairying than in other states. Farmers’ choice of the breed/breed type differs from state to state. Of the dairy type they prefer HF, LID and Maf than other types. Among beef types KK is the most preferred breed. KK is a small bodied local stable synthetic breed which predominates in number all through the region. Hot and humid climate as well as small holders extensive farming system in Malaysia seems to be unsuitable for raising Bos taurus genotypes. KK cattle demand conservation and genetic improvement. However, extensive studies involving breeds and types of cattle need to be undertaken towards development of suitable beef and dairy cattle breed pertinent to ECER, Malaysia.